2010
DOI: 10.1007/s00024-010-0141-x
|View full text |Cite
|
Sign up to set email alerts
|

Site-Specific Modeling of SH and P-SV Waves for Microzonation Study of Kolkata Metropolitan City, India

Abstract: Kolkata, one of the oldest cities of India, is situated over the thick alluvium of the Bengal Basin, where it lies at the boundary of the zone III and zone IV of the seismic zonation map of India. An example of the study of site effects of the metropolitan Kolkata is presented based on theoretical modeling. Full synthetic strong motion waveforms have been computed using a hybrid method that combines the modal summation and finite difference techniques. The 1964 Calcutta earthquake, which was located at the sou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 23 publications
1
8
0
Order By: Relevance
“…In contrast to this, 1-2 story buildings may suffer more damage in Rash Bihari Avenue area during local earthquakes. Very large amplification in low frequency range in Kolkata city (Vaccari et al 2011) and in Roorkee city (Singh 2009), both situated in Ganga basin, has been reported.…”
Section: Discussionmentioning
confidence: 95%
“…In contrast to this, 1-2 story buildings may suffer more damage in Rash Bihari Avenue area during local earthquakes. Very large amplification in low frequency range in Kolkata city (Vaccari et al 2011) and in Roorkee city (Singh 2009), both situated in Ganga basin, has been reported.…”
Section: Discussionmentioning
confidence: 95%
“…account, and it is therefore possible a detailed study of the wavefield that propagates even at large distances from the epicenter. The procedure is described in some detail by Panza et al (2001, and it has been employed in several studies worldwide (e.g., Ding et al 2004;Parvez et al 2003Parvez et al , 2006Zuccolo et al 2008;Mohanty et al 2009;Vaccari et al 2011). The input parameters to be specified are the seismic source parameters of an earthquake scenario and the structural models through which the seismic waves propagate from the source to the site of interest.…”
Section: Methodsmentioning
confidence: 99%
“…In the computation, we consider the earthquake of 12 June 1897, Shillong earthquake, M w = 8.1; focal mechanism: dip = 57 • , strike = 110 • and rake = 76 • ; focal depth = 9 km (Bilham and England 2001), located at a distance of about 460 km from Kolkata. Then, comparative analysis is made of the results obtained in this computation with earlier ones (Vaccari et al 2011) obtained considering the Calcutta earthquake that occurred on 15 April 1964, M w = 6.5; focal mechanism: dip = 32 • , strike = 232 • and rake = 56 • ; focal depth = 36 km (GSI 2000;Chandra 1977). In this paper the local seismic response in Kolkata city is analysed for two earthquake scenarios with different source mechanisms, one located near to Bay of Bengal and the other in the Shillong plateau.…”
Section: Introductionmentioning
confidence: 98%
“…The basin consists of fluviomarine sediment of a pericratonic Tertiary basin. The surficial geology in and around Kolkata is rather uniform, and is characterized by the presence of 10-15 m of silty clay, below which relatively coarser sediments occur that consist of either silt or clay with kunkar or sand (Vaccari et al, 2011). Geomorphologically, it is a typical deltaic flat land with surface elevation ranging between 5.5 and 9.5 m a.m.s.l sloping mostly southward.…”
Section: Geomorphology Of Kolkatamentioning
confidence: 99%